GREEN MOBILE COMMERCE ADOPTION IN VIETNAM: OPPORTUNITIES, CHALLENGES - Dang Van Tho (HUIT Journal of Science, 2025)
Green mobile commerce, or green m-commerce, has emerged as a competitive alternative for online shoppers due to the quick development of mobile technology and growing environmental concerns. Eco-friendly practices are being incorporated into mobile commerce (M-commerce) more and more as environmental concerns grow globally. The potential and difficulties of introducing green mobile commerce in Vietnam—a nation with a high smartphone penetration rate and rising environmental consciousness—are examined in this article. The study highlights current problems like inadequate infrastructure, low environmental literacy, and a lack of green consumer behavior while discussing the forces of technology, society, and regulations. Recommendations for businesses, academics, and political decision-makers to support a sustainable digital economy are included in the paper's conclusion.